Analisis dan Mitigasi Risiko Rantai Pasok Menggunakan House of Risk (HOR) dan Analytical Hierarchy Process (AHP) di PT Insan Citaprima Sejahtera - Gutawa, Ayyub Ihza; Pulansari, Farida (Ekonomis: Journal of Economics and Business, 2025)
This study aims to implement SCOR–HOR–AHP integration at PT. Insan Citaprima Sejahtera to identify risk agents and determine the most effective mitigation strategies. Risk data were analyzed using the House of Risk (HOR) and Analytical Hierarchy Process (AHP) methods. The results of this study revealed that risk analysis using the House of Risk method, stage 1 identified risk agent A40 (QC negligence) with the highest Aggregate Risk Potential value, namely 5484, which caused 12 risk events, including one event with a very severe impact (severity = 9). In stage 2, 24 risk agents causing 80% of the problems were grouped into 12 mitigation strategies, with priority given to routine training programs based on work modules (PA1). The selection of training types using the AHP method resulted in program C, namely face-to-face training between employees and supervisors through demonstrations and instructions, which was the most effective and efficient, with efficiency referring to flexible scheduling and cost savings.